Feed dan Filter, Strategi Komunikasi Islam Felix Siauw di Instagram - Ulfa Khairina (Ar-Raniry State Islamic University, Indonesia, 2020)
This study aims to review how the Islamic communication strategy carried out by Ust. Felix Siauw on Instagram as a media of preaching. As one of the famous da'i who is close to young people and active in social media, Felix Siauw has his own uniqueness in managing his social media accounts. This paper uses a qualitative descriptive description. Data collection techniques using documentation and observation. The determination of informant data is based on a purposive sampling technique. The number of informants used as the primary data consisted of the last 30 feeds consisting of photos and videos. The results showed that Ustadz Felix Siauw used Instagram by focusing on structuring feeds and using photo filters to attract millennials as mad'u (communicants). Ustadz Felix Siauw also uses effective communication in building Islamic communication with other Instagram users by writing communicative and informative captions as well as opening communication between users through communication styles, use of filters and feed settings, photos and videos, and captions.Kajian ini bertujuan melihat strategi komunikasi Islam yang dilakukan oleh Ust. Felix Siauw di Instagram sebagai media dakwah. Sebagai salah satu da’i kondang yang dekat dengan anak muda dan aktif di sosial media, Felix Siauw memiliki keunikan tersendiri dalam mengelola akun sosial medianya. Tulisan ini menggunakan penjabaran deskriptif kualitatif. Teknik pengumpulan data menggunakan dokumentasi dan observasi. Penentuan data informan dilakukan berdasarkan teknik purposive sampling. Jumlah informan yang dijadikan sebagai sumber data primer pada penelitian ini terdiri dari 30 feeds terakhir yang terdiri dari foto dan video Hasil penelitian menunjukkan bahwa Ustadz Felix Siauw menggunakan Instagram dengan memfokuskan pada penataan feeds dan penggunaan filter foto untuk menarik kaum milenial sebagai mad’u (komunikan). Ustadz Felix Siauw juga menggunakan komunikasi efektif dalam membangun komunikasi Islam dengan pengguna Instagram lain melalui penulisan caption yang komunikatif dan informatif sekaligus membuka komunikasi di antara pengguna melalui gaya komunikasi, penggunaan filter dan pengaturan feed, foto dan video, dan caption.